Mechanical thrombectomy of large vessel occlusion using adjustable vs. self-expanding stent-retriever—Comparison of Tigertriever device with stent-like stent-retrievers: A propensity score analysis - Piasecki, Piotr; Wierzbicki, Marek; Narloch, Jerzy; Dębiec, Aleksander; Staszewski, Jacek (Frontiers in Neurology, 2023)
Background: Stent-retrievers used for mechanical thrombectomy are self-expanding tubular stent-like devices with modified mesh structure for clot removal. Tigertriever is designed to provide manual control of its diameter and curvature. Methods: A retrospective single-center study was performed to compare Tigertriever with SolitaireX and pRESET (stent-like stent-retrievers group) using propensity score analysis. Patients treated in a comprehensive stroke center due to large vessel occlusion between January 2016 and August 2021 were evaluated. Baseline characteristics and treatment results were compared between these groups before and after pair matching Results: There were 140 patients (60 in Tigertriever and 80 in stent-like stent-retriever group). In propensity score analysis 52 matched pairs were selected in Tigertriever and stent-like stent-retriever groups. Tigertriever group had better successful first pass revascularization rate (46% vs 23%, OR (95% CI): 1.7 (1.1-2.9), p=0.013) and 14 minutes shorter groin-to-revascularization time (51 vs 65 min., p=0.017). There were no significant differences between Tigertriever and stent-like stent-retriever groups in: favorable mRS 3 months, favorable recanalization rate, symptomatic intracerebral hemorrhages. There were none observed periprocedural adverse events related to Tigertriever, SolitaireX or pRESET. Conclusions: Tigertriever had significantly better successful first pass revascularization rate and shorter groin-to-revascularization time in analysis done before and after propensity score matching with stent-like stent-retrievers. Tigertriever is comprable to stent-like stent-retrievers regarding mortality at 3 months, favorable mRS at three months, favorable recanalization rate or symptomatic cerebral hemorrhagic events.